Answer:
x= -2
x= -3
Step-by-step explanation:
x^2 +7x +10
when factored becomes
(x+2) (x+5)
the zeros are x +2 = 0, x = -2
x +5 = 0 x = -5
zeros are -2 and -5
The composite function G(F(x)) = x² + 4 is formed with these following original functions:
D. F(x) = x² and G(x) = x + 4.
<h3>How to find the composite function of f(x) and g(x)?</h3>
The composite function of f(x) and g(x) is given as follows:
![(f \circ g)(x) = f(g(x))](https://tex.z-dn.net/?f=%28f%20%5Ccirc%20g%29%28x%29%20%3D%20f%28g%28x%29%29)
For g of f(x), we have that:
![(g \circ f)(x) = g(f(x))](https://tex.z-dn.net/?f=%28g%20%5Ccirc%20f%29%28x%29%20%3D%20g%28f%28x%29%29)
For this problem, we have that:
G(F(x)) = x² + 4.
Which is possible with option D, as:
![G(F(x)) = G(x^2) = x^2 + 4](https://tex.z-dn.net/?f=G%28F%28x%29%29%20%3D%20G%28x%5E2%29%20%3D%20x%5E2%20%2B%204)
More can be learned about composite functions at brainly.com/question/13502804
#SPJ1
1/2x(25-7). Difference means to subtract. And then just multiply by 1/2 since it is asking for half.
Answer:
3 times larger
Step-by-step explanation:
I'm not a hundred percent sure but I'm pretty sure it is.
hope this helped ;)